2017
DOI: 10.1080/13670050.2017.1400516
|View full text |Cite
|
Sign up to set email alerts
|

Building bridges and strengthening positions: exploring the identity construction of immigrant bilingual teachers

Abstract: This study explores how bilingual teachers with an immigrant background construct professional identity in the context of initial literacy and second language teaching of adults. Specifically, the study seeks to understand what the teachers' membership of different workrelated communities means for their professional identity and what capital the teachers use, negotiate and acquire to strengthen their positions in this professional field. The study is based on interviews with seven bilingual teachers. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Key qualities are the SCLs' experiences of migration, of learning the Swedish language and of settling in Sweden. The value of migration experiences is also emphasised by Colliander (2020) and Rubenstein Reich and Jönsson (2006). In arranging such learning, these qualities have been shown to incur participants' trust, and on the basis of these experiences the SCLs often view themselves, and are seen by the participants, as role models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key qualities are the SCLs' experiences of migration, of learning the Swedish language and of settling in Sweden. The value of migration experiences is also emphasised by Colliander (2020) and Rubenstein Reich and Jönsson (2006). In arranging such learning, these qualities have been shown to incur participants' trust, and on the basis of these experiences the SCLs often view themselves, and are seen by the participants, as role models.…”
Section: Discussionmentioning
confidence: 99%
“…In such work, as it has been pointed out, the qualities of teachers become important, not least teachers' own experience of migration and of settling in a new country of residence, i.e. their personal qualities (Colliander, 2020Rubenstein Reich & Jönsson, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…However, immigrant teachers themselves may want to emphasize their professional role as teachers even though they also are willing to mediate relations between home and school. They struggle for professional respect and see their position as marginalized and insecure, often face discrimination and sometimes feel their background is seen as a handicap (Colliander, 2017;Virta, 2015;Lefever et al, 2014).…”
Section: Contexts Of the Study: Finland And Swedenmentioning
confidence: 99%
“…In one study of asylum-seeking students in Australia, authors suggested that "the form of human capital that counts the most [for displaced students] is proficiency in the host language;" [58] (p. 8), particularly because language speaking skills were often eligibility requirements for hiring. In other words, the hegemony of certain languages in resettlement contexts was exacerbated, amplified, and made structural by institutional hiring policies and practices that favored students speaking a dominant language and the perception that non-native speakers with accents are incapable [25][35] [37][80] [88]. Otherness and discrimination like this made displaced students feel conscious about their language and therefore continually "under pressure to do the right thing, say the right thing, and behave in the right way to help them get inside the circle" [82] (p. 6).…”
Section: Othering Through Discoursementioning
confidence: 99%